Tales from the hood - Buckley, Michael, 1969- (Buckley, Michael, 1969- Sisters Grimm, 2008)
When a kangaroo court of Everafters, led by Judge Mad Hatter, tries Mr. Canis for his past crimes as the Big Bad Wolf, the Grimms seek evidence to save their friend, although Sabrina questions whether he should be saved.